EFFECTIVENESS OF MOBILE APPLICATIONS IN HEALTHCARE - Ermetov E. Ya.; Fazliddin Arzikulov (International Journal of Innovations in Engineering Research and Technology, 2025)
The development of the digital economy drives the transformation of all areas of socio-economic activity, including healthcare. One of the most rapidly developing areas is the use of mobile applica-tions as a tool to increase the efficiency of medical services. This article examines the role of mobile digital solutions in the healthcare system as an element of digital infrastructure. It analyzes the func-tional capabilities of medical mobile applications, their impact on user behavior, and the optimization of healthcare delivery processes. Special attention is paid to assessing the effectiveness of such ap-plications in the context of improving access to medical services, enhancing the quality of prevention and monitoring of chronic diseases, as well as fostering digital skills among the population. The arti-cle also discusses the prospects for further integration of mobile solutions into the healthcare economy and the need for regulatory frameworks in the context of digital transformation. The research findings highlight the significance of mobile technologies as a driver of sustainable healthcare development in the digital economy.